Knowledge, attitude and practice on regional food among families of preschool children - Marcela Lima Silveira; Mariana Cavalcante Martins; Emilly Karoline Freire Oliveira; Emanuella Silva Joventino; Lorena Barbosa Ximenes (Rev Rene)
We aimed to verify the knowledge, attitude and practice on the use of regional food of families of preschool children at a rural area. Descriptive-exploratory study with quantitative approach, conducted with 200 families of preschool children, residing in two rural districts of Maranguape-CE, Brazil. We applied a Knowledge, Attitude and Practice survey, focusing on the use of regional food. The districts presented similarities with regard to gender (p=1.000), marital status (p=0.603), education (p=0.349), number of preschool children (p=0.104), and workplace (p=0.632), but had different results regarding family income (p=0.033). As for the regional foods, there was no statistically significant association in knowledge (p=0.731), attitude (p=0.362), and practice (p=0.600) in the study locations, prevailing the inadequate level in the three axes. We verified that the people responsible for preschool children in the two locations were unaware of the regional foods terminology and presented inappropriate knowledge, attitude and practice regarding their use.